RANCANG BANGUN ALAT PENDETEKSI DINI PONTENSI KEBAKARAN SECARA OTOMATIS pada RUANGAN TERINTGRASI dengan INTERNET of THINGS - Udoyono, Kodar; Daniati, Dewi Nia (STMIK Subang, 2023)
In an effort to enhance safety and early detection of potential fires in indoor spaces, this research designs and constructs an automatic early fire detection device integrated with the Internet of Things (IoT). The device incorporates a flame sensor, MQ2 sensor, DHT11 temperature and humidity sensor, buzzer, LCD 16x2, and Node MCU to provide an effective and efficient solution. The flame sensor is utilized to detect the presence of fire, while the MQ2 sensor is employed to detect potentially hazardous gases associated with fires. The DHT11 sensor provides temperature and humidity information in the surrounding environment, aiding in identifying potential conditions conducive to fires. The Node MCU serves as the central processing unit of the system, collecting data from the sensors and transmitting it to the IoT platform via Wi-Fi connectivity. This data can be accessed and monitored in real-time through applications or online platforms. Upon detecting a potential fire, the buzzer issues an audible alert, and the LCD 16x2 displays detection information for the user. The primary advantage of this device lies in its ability to provide prompt and efficient detection information, accessible remotely through internet connectivity. With the integration of IoT, the device offers a smarter and more responsive solution for addressing potential fires in indoor spaces. The implementation of this device is anticipated to enhance safety and provide better protection against the risk of fires.